FRI0130 Relationship between presence of neurological symptoms and activity of systemic lupus erythematosus. (1st June 2001) - Ostanek, L; Honczarenko, K; Fischer, K; Fiedorowicz-Fabrycy, I
Abstract : Background: According to many authors presence of neurological symptoms are features of disease activity in patients with systemic lupus erythematosus. Clinical observations very often do not confirm this hypothesis. Objectives: To assess if neurological symptoms correlate with disease activity in patients with systemic lupus erythematosus. Methods: The study was performed on 83 patients with SLE (77 women and 6 men), age 17–63 years mean age 33, 8 yrs), disease duration was 1–30 years (mean 9, 05 yr). Every subject was assessed at least two times by rheumatologist and neurologist during different stages of SLE activity. SLE activity was assess according to SLEDAI scale. Haematological, biochemistry and coagulation tests were performed for everyone. In some cases histopatolgical assessment of tissue samples were done. Electrophysiological tests (EEM, EMG, BAEP, VEP) and cerebral CT, MRI and SPECT scans were performed in subjects with neurological symptoms. All the subjects were tested for the presence of antinuclear antibodies, (ANA), anticardiolipin antibodies (aCL), anti-B2-glycoprotein antibodies and antiendothelial antibodies (AECA). Results of the mentioned tests were statistically evaluated. Results: No association has been found between presence of neurological symptoms and disease activity in patients with systemic lupus erythematosus Neurological symptoms were found significantly more frequently in subjects with high titer of IgG anticardiolipin antibodies and in patients with secondary antiphospholipid syndrome. There was a tendency for neurological symptoms to occur in patients with vascular complications. Conclusion: